The next phase of European climate policy: Laying the groundwork with the 2040 target - Felix Schenuit; Oliver Geden (Stiftung Wissenschaft und Politik (SWP), 2024)
The outgoing European Commission has published its Communication on a 2040 climate target as its last major climate policy initiative before the 2024 European elections. By recommending a net emissions reduction target of 90 per cent compared to 1990 levels, it lays the strategic foundations for the forthcoming legislative period. At the same time, the policy initiative takes the opportunity to emphasise the growing importance of the interplay between industrial and climate policy, particularly with regard to carbon management technologies. Although reforming the EU's climate policy architecture for the years 2031 to 2040 will not begin until after the upcoming European elections, the Communication offers a glimpse into the political challenges that the German government will also have to face.
Keywords: 320; European climate policy; 2040 target; emissions reduction; carbon management technologies; greenhouse gas neutrality